EP.TU.533A rare clinical presentation of Goblet Cell Adenocarcinoma of the appendix: Recommendations for safe & effective management. (28th October 2021) - Ramsamy, Ganeshan; Slack, Zoe; Tebala, Giovanni
Abstract: Background: Goblet cell carcinoma (GCC) is a rare mixed neoplasm arising from the appendix, consisting of glandular and neuroendocrine tissue. It typically presents in adults with a mean age of 55-65 years old. Diagnosis is usually incidental via histopathological examination after 0.3% to 0.9% of all appendicectomies. Literature remains sparse on classification and prognosis of GCC, and cases documented in younger patients. Aims: To highlight an interesting clinical presentation and intra- and post-operative management of GCC. To increase awareness for future practice when managing patients with GCC. Methods: A 37 year-old male presented with left sided abdominal pain, constipation and fresh rectal bleeding. Computed Tomography demonstrated extensive SMV thrombus causing small bowel ischaemia. On the Intensive Care Unit, he underwent thrombolysis through a Transjugular Intrahepatic Porto-Systemic Shunt. A few days later, he developed bowel obstruction, necessitating a small bowel resection secondary to an ischaemic stricture. 9 months later, he presented with clinical signs of appendicitis. After an uneventful appendicectomy, he was diagnosed with GCC upon histopathological examination of the specimen. Results: The patient made an uneventful post-operative recovery. A multidisciplinary team (MDT) decision was made to perform a completion right hemicolectomy, with histology confirming pT3N1M0 GCC. Adjuvant chemotherapy with 5-Fluorouracil was started. Conclusion: This case highlights GCC with a preceding clinical course not yet published in the literature. It stresses the importance of the MDT in managing GCC. Although primarily diagnosed histologically, a clinical suspicion of GCC of the appendix is worth considering in pro-thrombotic patients.